PERAN PEMERINTAH DESA DALAM PENGELOLAAN DANA DESA MENURUT PERSPEKTIF SYARIAH PADA DESA RINGINPITU KABUPATEN TULUNGAGUNG - erika Indah Sastiya Putri; Sri Dwi Estiningrum (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2022)
Abstract The goal of this research is to establish the Village Government's responsibilities for the proper management of the Village Fund, including its planning, implementation, administration, accountability, and reporting. This research is categorized as a qualitative research based on the results of interviews and observations. Village officials who are involved in the administration of village funds are the informants in this study. According to the study's findings, village governments play a role in the administration of village funds, and they do so in accordance with Islamic law, which places a premium on the welfare of communities in accordance with the four traits of the Prophet. This is evidenced by the government conducting open deliberation and evidence of reporting activities accompanied by the Treasurer and approved by the Village Head.